2015
DOI: 10.1007/s00040-015-0390-x
|View full text |Cite
|
Sign up to set email alerts
|

Ectaheteromorph ants also host highly diverse parasitic communities: a review of parasitoids of the Neotropical genus Ectatomma

Abstract: Despite the diversity of ant-myrmecophile associations, there are few examples of primary parasitism of ants and these are poorly documented, particularly in genera with only a few species such as the genus Ectatomma. We identified 18 associations that involve at least 16 taxa of primary parasitoids distributed in three families belonging to two invertebrate classes, and five of the 15 valid Ectatomma species. Among these, we report for the first time an endoparasitoid fly (probably a phorid) that attacks E. r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 91 publications
0
10
0
2
Order By: Relevance
“…The above two species are known to be sympatric only in a region situated on the coastal plain near the border between Chiapas in Mexico and Guatemala. Previous studies have revealed that both species have similar life traits in this region, including feigning of death when workers are disturbed (Cupul‐Magaña, ) and presence of the same parasitoid eucharitid wasp species (Pérez‐Lachaud et al ., ; Lachaud & Pérez‐Lachaud, ). However, ongoing research supports that, in addition to the presence/absence of microgyny, the two species can also be discriminated from each other by other biological traits, such as date of sexuals production (J.‐P.…”
Section: Discussionmentioning
confidence: 99%
“…The above two species are known to be sympatric only in a region situated on the coastal plain near the border between Chiapas in Mexico and Guatemala. Previous studies have revealed that both species have similar life traits in this region, including feigning of death when workers are disturbed (Cupul‐Magaña, ) and presence of the same parasitoid eucharitid wasp species (Pérez‐Lachaud et al ., ; Lachaud & Pérez‐Lachaud, ). However, ongoing research supports that, in addition to the presence/absence of microgyny, the two species can also be discriminated from each other by other biological traits, such as date of sexuals production (J.‐P.…”
Section: Discussionmentioning
confidence: 99%
“…Se os parasitoides permanecem dentro da colônia por algumas horas, as formigas mostram apenas uma moderada agressividade a eles (LACHAUD; PEREZ-LACHAUD, 2012;LACHAUD et al, 1998), o que pode ser resultado tanto de adaptações morfológicas como de mimetismo químico dos parasitoides (LACHAUD et al, 1998;HOWARD et al, 2001;PÉREZ-LACHAUD et al, 2015). Espécies do gênero Dilochanta, por exemplo, possuem uma depressão no escutelo que pode estar associada a secreções que provavelmente têm alguma relação com a ausência de agressões aos parasitoides em suas primeiras horas de vida dentro do ninho (LACHAUD et al, 1998;.…”
Section: Eucharitidaeunclassified
“…Os parasitoides normalmente emergem das pupas dentro do ninho de seus hospedeiros e podem sair por si só, ou ser carregados para fora das colônias pelas formigas como se fossem lixo (LA-CHAUD et al, 1998;PÉREZ-LACHAUD et al, 2006a;TORRÉNS, 2013). Se os parasitoides permanecem dentro da colônia por algumas horas, as formigas mostram apenas uma moderada agressividade a eles (LACHAUD; PEREZ-LACHAUD, 2012;LACHAUD et al, 1998), o que pode ser resultado tanto de adaptações morfológicas como de mimetismo químico dos parasitoides (LACHAUD et al, 1998;HOWARD et al, 2001;PÉREZ-LACHAUD et al, 2015). Espécies do gênero Dilochanta, por exemplo, possuem uma depressão no escutelo que pode estar associada a secreções que provavelmente têm alguma relação com a ausência de agressões aos parasitoides em suas primeiras horas de vida dentro do ninho (LACHAUD et al, 1998;.…”
Section: Eucharitidaeunclassified